Making more from goat hides - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
Value of goat hides, protecting goat hides from damage, good storage, and the importance of processing rather than exporting raw hides.